2016
DOI: 10.3311/ppci.7767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prewetted Pumice Aggregate Addition on Concrete Properties under Different Curing Conditions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The main observation is that the bulk density values of cement pastes containing pumice are less than those of control paste (mix I) and the difference between them increases as the pumice content in the blended pastes increase. This result may be attributed to the partial replacement of cement by a lighter blender [37]. Evidently, all tested specimens incorporated with Ni 2+ or Co 2+ ions showed higher and/or comparable bulk densities values at 1 and 28 days of hydration compared to those of the corresponding hardened pastes free from these ions.…”
Section: Bulk Density and Total Porositymentioning
confidence: 79%
“…The main observation is that the bulk density values of cement pastes containing pumice are less than those of control paste (mix I) and the difference between them increases as the pumice content in the blended pastes increase. This result may be attributed to the partial replacement of cement by a lighter blender [37]. Evidently, all tested specimens incorporated with Ni 2+ or Co 2+ ions showed higher and/or comparable bulk densities values at 1 and 28 days of hydration compared to those of the corresponding hardened pastes free from these ions.…”
Section: Bulk Density and Total Porositymentioning
confidence: 79%
“…The porous structure of pumice is due to the formation of bubbles or air voids when gases contained in the molten lava flowing from volcanoes are entrapped on cooling [23]. About 40% of world pumice reserves are present in Turkey [24] which provides several opportunities for its efficient utilization in concrete generally as a lightweight aggregate [25][26][27][28] or as a cement replacement material [23,24,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the same study [26], at the end of 300 freezing and thawing cycles, porosity was increased up to 12% for high strength concrete incorporating PA. Gökçe et al [27] stated that lightweight reactive powder concrete can be developed with including pumice as fine aggregate (size 0-1 mm) with the compressive strength of 69 and 176 MPa. Kabay et al [28] determined lower mechanical performance of concretes incorporating 50% and 100% pumice (size 1-4 mm). Hossain et al [18] observed 28%, 27% and 30% reduction at 28 days for compressive strength, modulus of elasticity and tensile strength with including pumice (size 0.15-4.75 mm), respectively.…”
Section: Introductionmentioning
confidence: 99%